Ascertaining the Effectiveness of Coordination Training Interventions in Enhancing Sports Performance: A Systematic Review and Meta-analysis - Saini, Ashwani; Dubey, Bipin Kumar; Vishwakarma, Rakesh (Physical Education Theory and Methodology, 2025)
Objectives. The study aimed to analyze the effects of training programs that focused on various coordination exercises to improve the sports performance and coordination of athletes. Materials and methods. An electronic review was conducted to compile the literature related to this issue, using Scopus, PubMed, Google Scholar and ProQuest databases. Following a systematic search, eleven studies carried out between 2014 to 2024 were considered appropriate for meta-analysis and were retrieved and analysed. The studies included were confined to different coordination interventions, such as balance, rhythm, agility, neuromuscular training, jump ropeladder exercises, spatial orientation, non-sports specific and proprioceptive training, ranging from 6 weeks to an annual macrocycle with participants (sub-junior and junior levels) from different sports. Results. The meta-analysis revealed a small effect size improvement for balance training (E = 0.38; 95 % CI = -0.66-2.54; p = 0.25), a large effect size and significant enhancement for coordination and rhythm training (E = 2.2; 95 % CI= -0.98-1.45; p = 0.70). Additionally, it was noted a moderate effect size and substantial improvement for a specific coordinative ability training (E = 1.8; 95 % CI = -0.84-2.99; p = 0.00) when compared the experimental group with the control group. The results of 11 studies established a significant effect size of various coordination training interventions in improving motor coordination of athletes. However, the impact of these interventions on sports skills and performance remains limited and inadequate. Conclusions. After a thorough analysis, it was concluded that various training regimens involving different stimuli, means and methods, comprising proprioceptive training, spatial training, motor rhythm training, neuromuscular training, balance training, coordination training drills using ladders, wobble board, bosu balls, trampoline and dynamic games, as well as non-specific sports training with basic exercises, have been found to be effective in enhancing motor coordination and sports skills.